1980
DOI: 10.1111/j.1460-2695.1980.tb01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Self-Similarity of Fatigue in the Linear Range of Crack Growth

Abstract: The application of dimensional analysis and similarity methods to the study of the speed of fatigue crack growth is considered. It is shown that the Paris range of the crack propagation diagram is an intermediate-asymptotic stage of the crack growth process. Over this stage the influence of the initial conditions on the process of fatigue crack growth has disappeared but the influence of the instability has not yet intruded. So-called incomplete self-similarity prevails at this stage with respect to a basic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 8 publications
0
55
0
Order By: Relevance
“…In this less restrictive form, it is apparent that considerations of similarity imply that both the C and m constants in the Paris law are not simply a function of the material properties and the nature of the applied loading, but also on specimen size, h, through the basic similarity parameter Z. Indeed, comparison with Heiser and Mortimer data (Heiser and Mortimer, 1972) on 4340 steel revealed such a relationship between m and Z, as predicted by Equations (5) and (6) (Barenblatt and Botvina, 1981). One aim of the present study is to explain such a result in terms of physical mechanisms.…”
Section: Dimensional and Similarity Analysismentioning
confidence: 70%
See 1 more Smart Citation
“…In this less restrictive form, it is apparent that considerations of similarity imply that both the C and m constants in the Paris law are not simply a function of the material properties and the nature of the applied loading, but also on specimen size, h, through the basic similarity parameter Z. Indeed, comparison with Heiser and Mortimer data (Heiser and Mortimer, 1972) on 4340 steel revealed such a relationship between m and Z, as predicted by Equations (5) and (6) (Barenblatt and Botvina, 1981). One aim of the present study is to explain such a result in terms of physical mechanisms.…”
Section: Dimensional and Similarity Analysismentioning
confidence: 70%
“…Since in the original analysis of Barenblatt and Botvina (1981) only a single set of experimental data was considered, we first examine a large body of fatigue-crack growth rate results in order to interrogate relationships between the Paris exponent m and specimen dimensions. To facilitate this approach, we use the compilation of ambient-temperature data from the work of Ritchie and Knott (1973), based on experimental fatigue-crack propagation studies at ambient temperatures on a wide range of steels from (Carman and Katlin, 1966;Wei et al, 1967;Crooker et al, 1968;Miller, 1968;Bates et al, 1969;Crooker and Lange, 1970;Clark and Wessel, 1970;Evans et al, 1971;Ritchie and Knott, 1973).…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
“…L.R. Botvina, processing the data by Heiser and Mortimer [33] (see [32]), and R.O. Ritchie [34], processing the data by Knott and Ritchie [35] (Figures 7 and 8), showed that the dependence of m upon Z, i.e., upon the specimen size can be substantial.…”
Section: Paris Law -An Example Of Incomplete Similaritymentioning
confidence: 99%
“…For the vast majority of cases m is substantially larger than 2. Assuming incomplete similarity we obtain [32] (see also [16]):…”
Section: Paris Law -An Example Of Incomplete Similaritymentioning
confidence: 99%
See 1 more Smart Citation